Estrategias metodológicas activas en el proceso enseñanza aprendizaje de Ciencias Naturales para la mejora del rendimiento académico. Año lectivo 2022-2023 - Aguilar Romero, Briggette Isabel (2023)
Active methodological strategies are fundamental in the development of the classroom process because they generate significant learning in students, through dynamic, motivating and participatory processes, in such a way that they allow improving learning results. The aim of this research was: To enhance the academic performance of students through active methodological strategies, which stimulate motivation and interest in learning Natural Sciences, in the eighth year of EGB, of the "27 de Febrero" High School. ”, during the 2022 – 2023 school year The method used in the research was inductive; since, from direct observation, the problem was identified, for its subsequent intervention; According to the approach, it is qualitative because the teaching-learning strategies, the behavior of the educational actors and the learning results are characterized, in order to propose alternative solutions; In addition, the research corresponds to the type of participatory action research, because the researcher executed the intervention proposal in the classroom, getting directly involved with the object of study in order to meet the proposed objectives; Regarding the temporality of the investigation, it is transversal; since, it was developed in a relatively short time. The results obtained through the survey indicated that the active methodological strategies implemented, in the development of the PEA of Natural Sciences, were effective, it was possible to build an active, motivating and significant learning; It should be noted that the didactic techniques and resources applied, to make the implemented strategies viable, contributed to awakening motivation and interest in students for learning, which led to the improvement of their academic results. It is concluded that through the implementation of active methodological strategies, motivation and interest in the study of Natural Sciences are promoted in students and, with this, they improve their academic performance. Keywords: active learning, meaningful learning, methodological strategies Natural Sciences.